Re-take of Amrita : digital photomontages based on photographs by Umrao Singh Sher-Gil (1870-1954) and photographs from the Sher-Gil family archive - Sundaram, Vivan; Sher-Gil, Umrao Singh, 1870-1954. (New Delhi : Tulika, 2001)
On life and times of Indian painter, Amrita Sher-Gil, 1913-1941 and her father and photographer, Umrao Singh Sher-Gil (1870-1954).
Keywords: Sher-Gil, Umrao Singh, -- 1870-1954.; Photomontage -- Catalogs; Photomontage -- India -- History